Problems and Progressive Cryptanalysis of Prominent Block Ciphers - Shoukat, I.A.; Iqbal, U.; Malik, M.S.A.; Sahar, F. (The Nucleus, 2020)
Practical cracking of Data Encryption Standard (DES) and mathematical cracking of Advanced Encryption Standard (AES) is seriously questionable despite the fact that AES retains good length of the encryption key, but still all encryption rounds have been cracked mathematically. Therefore, there is a need to revisit the cracking excursion of these well-known cryptosystems to inquire into potential discrepancies associated with them and to evolve the design of future block ciphers. Thus, this study aims to enlighten the cryptanalysis journey of AES and DES, including all DES variants (TDES, DESX and DEX+) to discuss latent weaknesses, issues and problems associated with these block ciphers. To accomplish this review task, quality of related studies was collected from several well-known research repositories and each study was critically analyzed. Earlier review-efforts were found relatively marginal in scope, capacity and are not up-to-date with the latest issues, and cryptanalysis results thereby differ with this work. The resultant discussion shows that known parameters like static substitution, static permutation, fixed block size and repeated encryption rounds with a similar set of encryption operations support the crackers in executing effective cryptanalysis in symmetric block ciphers. Therefore, encrypting the secret data with too many repeated encryption rounds with identical encryption operations is not as effective in enhancing the security of symmetric block cipher as it is usually believed.